2013
DOI: 10.1007/s00381-013-2117-5
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in children and adolescents with spinal dysraphism: results from a Taiwanese sample

Abstract: Children and adolescents with MMC have reduced HRQL compared with those with LMMC. Children and adolescents with more associated medical problems have the greatest risk of diminished physical and psychosocial well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…The CHQ‐PF50, a parent‐report instrument, was used to measure children's HRQOL in nine studies. Paralleling findings of studies that have used PedsQL, parents of children with MMC reported significantly lower scores on the physical and psychosocial aspects of CHQ‐PF50 than did parents of healthy children (Rendeli et al ; Wood et al ; Bartonek et al ; Tezcan et al ; Wang et al ; Turkucuoglu & Simsek ; Midrio et al ). Few studies indicated that MMC did not affect the following aspects of patient's life: self‐esteem, behaviour (Danielsson et al ) and family cohesion (Danielsson et al ; Law et al ).…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…The CHQ‐PF50, a parent‐report instrument, was used to measure children's HRQOL in nine studies. Paralleling findings of studies that have used PedsQL, parents of children with MMC reported significantly lower scores on the physical and psychosocial aspects of CHQ‐PF50 than did parents of healthy children (Rendeli et al ; Wood et al ; Bartonek et al ; Tezcan et al ; Wang et al ; Turkucuoglu & Simsek ; Midrio et al ). Few studies indicated that MMC did not affect the following aspects of patient's life: self‐esteem, behaviour (Danielsson et al ) and family cohesion (Danielsson et al ; Law et al ).…”
Section: Resultssupporting
confidence: 55%
“…Six studies using generic HRQOL instruments indicated no significant relationships between bowel or bladder continence and children's HRQOL (Lemelle et al ; Dodson et al ; Ramachandra et al ; Freeman et al ; Muller‐Godeffroy et al ; Rocque et al ). In contrast, another three studies that also used the generic HRQOL measurements confirmed such correlations (Rendeli et al ; Olesen et al ; Wang et al ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Patients with a MMC had lower scores on physical and psychosocial aspects. Children with a higher lesion level had poorer physical health, but not poorer psychosocial health 13 . Studies have described the capacity, or lack thereof, of ambulation based on the lesion level, cognition, functional independence and quality of life separately, but no studies have described, simultaneously, gross motor function, cognition, functional independence and quality of life, or investigated their relationships in patients with MMC.…”
mentioning
confidence: 84%